Successful Outcome of a Triplet Gestation in a Patient with a History of an Open Maternal-Fetal Surgery - Kathleen A. Rivers; Paul W. Whitecar; Cristóbal S. Berry-Cabán (Case Reports in Medicine)
Reproductive outcomes in women after pregnancy complicated by an open maternal-fetal surgery (OMFS) are limited. A review of the medical literature reveals only isolated cases of successful multiple pregnancies, and there are no prior documented cases of successful triplet gestations following OMFS. We report the delivery of a triplet gestation at 34-week gestation in a patient with a history of previous OMFS.